Skeletal myopathy in patients with chronic heart failure: significance of anabolic‐androgenic hormones. Issue 4 (1st August 2014) - Josiak, Krystian; Jankowska, Ewa A.; Piepoli, Massimo F.; Banasiak, Waldemar; Ponikowski, Piotr
Abstract : In heart failure, impairment of cardiac muscle function leads to numerous neurohormonal and metabolic disorders, including an imbalance between anabolic and catabolic processes, in favour of the latter. These disorders cause loss of muscle mass with structural and functional changes within the skeletal muscles, known as skeletal myopathy. This phenomenon constitutes an important mechanism that participates in the pathogenesis of chronic heart failure. both its clinical symptoms and the progression of the disease. Attempts to reverse the above‐mentioned pathologic processes by exploiting the anabolic action of androgenic hormones could provide a potentially attractive treatment option. The current concepts of anabolic androgen deficiency and resultant skeletal myopathy in patients with heart failure are reviewed, and the potential role of anabolic‐androgenic hormones as an emerging therapeutic option for targeting heart failure is discussed.